PERAN MAHASISWA APOTEKER UHO DAN BNN DALAM CEGAH PENYALAHGUNAAN NARKOBA SINTESIS SERTA EDUKASI BAHAYA ROKOK ELEKTRIK YANG MENGANCAM GENERASI MUDA GUNA MEWUJUDKAN GENERASI SEHAT TANPA NARKOBA - Kasmawati, Henny; Indalifiany, Astrid; Sida, Nurramadhani A.; Puriandani, Ketut Ayu; Pratiwi, Dinda; Fauziah, Nining; Azis, Nurul Ella Kholifatul; Widari, Niluh Putri Sri; Putri, Egi Alisa; Mulya, Elzah; Trihafsari, Hanin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The abuse of synthetic drugs and the increasing use of electronic cigarettes among adolescents pose a serious threat to public health and the future of young generations. Limited awareness of the dangers of synthetic drugs and the misconception that electronic cigarettes are safer than conventional cigarettes contribute to adolescents’ vulnerability. This community service program aimed to enhance students’ knowledge and awareness of the risks associated with synthetic drugs and electronic cigarette use through collaboration between Pharmacy Students of Universitas Halu Oleo and the National Narcotics Agency. The program employed educational counseling, interactive lectures, and question-and-answer sessions tailored to adolescent characteristics. The materials covered types and health impacts of synthetic drugs, risks of electronic cigarette use, and students’ roles in preventing drug abuse in school environments. The results showed improved knowledge, increased awareness, and stronger commitment among students to avoid synthetic drugs and electronic cigarettes. Active participation during discussions demonstrated the effectiveness of collaboration between educational institutions and government agencies in strengthening drug abuse prevention and promoting healthy lifestyle behaviors.